1989
DOI: 10.1088/0953-8984/1/20/004
|View full text |Cite
|
Sign up to set email alerts
|

On the character of defects in GaAs

Abstract: Positron lifetime measurements on GaAs are presented and discussed and former measurements are reviewed. The limitations and appropriate criteria for adequate spectrum analyses are considered in detail. It is shown that exceptionally good statistical accuracy is necessary for a reliable and consequential decomposition, and that source corrections are very important. Results for liquid phase electro-epitaxially grown GaAs conclusively show that the bulk lifetime for GaAs is 220+or-1 ps. All other GaAs samples (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…This spectrum was subject to analysis with a four component fit, the first two components being fixed at the spectrum found for the GaAs using the intensity ratio constraint facility of POSI-TRONFIT. The remaining two components gave the [23] we associate the longer of the two components with annihilation in the NaCI, whereas the shorter of the two is similar to that observed by other workers [24] and may be attributed to defected Ni. Finally after the source and background corrections, it was found that all lifetime spectra were fitted well by the sum of two exponential components: …”
Section: Results With Dc-applied Biassupporting
confidence: 89%
See 2 more Smart Citations
“…This spectrum was subject to analysis with a four component fit, the first two components being fixed at the spectrum found for the GaAs using the intensity ratio constraint facility of POSI-TRONFIT. The remaining two components gave the [23] we associate the longer of the two components with annihilation in the NaCI, whereas the shorter of the two is similar to that observed by other workers [24] and may be attributed to defected Ni. Finally after the source and background corrections, it was found that all lifetime spectra were fitted well by the sum of two exponential components: …”
Section: Results With Dc-applied Biassupporting
confidence: 89%
“…This spectrum was analyzed using POSI-TRONFIT [22] and found to be well represented by two lifetime components (404 ps at 3.5% and 223 ps at 96.5%). Following the work of Dannefear, et al on GaAs [23] with Field-assisted positron m o d e r a t o r varying levels of 22NaCI activity, we take this lifetime spectrum to be totally representative of the semi-insulating GaAs and not noticeably perturbed by annihilations in the NaC1. The lifetime spectrum was then taken for the same SI-GaAs samples (the 1.5 ~tCi source removed) using the 28 pCi Ni foil encapsulated source.…”
Section: Results With Dc-applied Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Each lifetime spectrum contained 3 × 10 6 counts and was analyzed using the program of POSITRONFIT [8]. Due to the low activity of directly deposited source there was no need to carry out any source correction for annihilations in the micro-crystals of radioactive salt [9].…”
Section: Introductionmentioning
confidence: 99%
“…Because of this unique character, the study of defects in compound semiconductors by positron annihilation techniques is a subject of increasing interest [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%